The efficiency of school-parent associations (SPA) at schools - Ozmen, Fatma; Canpolat, Cevdet (Elsevier Science Bv, 2010)
It is an imperative for schools to cooperate with various social units and organizations in order to achieve effective education at schools. In this context, Parent-Teacher Associations (PTA) or School Parent Associations (SPA) as in Turkey, can work closely with the parents, teachers, administrators, and other community members to provide support for the improvement of education and student performance. The main goal of that research is to determine the efficiencies of school-parent associations at schools, according to the views of principals, teachers, and of parents, who take part in SPAs. The analysis of the data revealed that the contribution of SPAs in the determined dimensions were not so efficient in this research. Some recommendations were made concomitant with the results. (C) 2010 Published by Elsevier Ltd.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: School-parent associations; efficiency; principals; teachers; parents